Perancangan Aksesoris Interior Menggunakan Bahan Limbah Serbuk Rotan - Meilyana Darmawan; Adi Santosa; Jean Francois Poilot (Intra, 2018)
Abundant availability of rattan raw materials in the country results to the production of rattan products waste in the form of rattan powder. The rattan powder waste is made into a rattan powder board to perform material efficiency as an act of environmental care. As rattan powder was only used as a fuel on heating rattan, a test needs to be done in advance to find out the final product result and the target market. The design method used includes observation, programming, design concept, experiment, design schematic, final design, prototype, and business plan. The processing of rattan waste into rattan powder board is applied into decorative interior accessories. The rattan powder waste processed in an industrial way using press machine to create a rattan powder board with a natural final look. The advantages of interior accessories design made from rattan powder board is that it could improve the image and leads to a higher selling value.